Política pública e plantas medicinais, fitoterápicas e saberes tradicionais: contribui- ção de um estudo teórico - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The use of plants for medicinal purposes, for the treatment, cure and prevention of diseases is an ancient practice in the Amazon region. The general objective of this study is to describe the relationship between traditional knowledge about medicinal and phytotherapeutic plants, based on the National Policy on Medicinal and Phytotherapeutic Plants. The specific objectives are: to map some experiences of traditional populations with medicinal plants; to identify the public policy aimed at the inclusion of medicinal and phytotherapeutic plants in the Living Pharmacy. The study is bibliographical, carried out in the scientific field of medicinal plants in the Amazon region and the experiences of the Living Pharmacy. The study is characterized as a literature review, of the narrative and qualitative type. It used secondary data and research from studies and scientific works published in databases of scientific relevance journals available in electronic databases, such as: Scielo, Lilacs, Google Scholar and Medline, and printed books. Data analysis was carried out from a critical perspective, seeking to understand the challenges of public management in the Living Pharmacy and the valorization of knowledge about medicinal plants. The results of this study show that traditional knowledge is transmitted throughout the generations of a given people and can provide important data for new scientific research on the use of medicinal plants. It is concluded that encouraging the expansion of training for health professionals on the importance of medicinal plants in the treatment of human health, as well as expanding knowledge about the National Policy on Medicinal Plants and Phytotherapeutics, and about protocols and practices in care provided by the SUS (Unified Health System). Finally, it is believed that it is important to reflect and expand discussions on the creation of public policies for remote areas such as the Amazon.
Keywords: Política pública; Saberes tradicionais; Plantas medicinais e fitoterápicos; Farmácia Viva; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS